Cranial morphology in the brachygnathic sheep. Issue 1 (December 2016) - Eriksen, T.; Ganter, M.; Distl, O.; Staszyk, C.
Abstract Background Craniofacial morphology of sheep with phenotypically observed mandibular distocclusion was analysed using the multivariate techniques principle component analysis and cluster analysis in order to test whether different types of craniofacial malformations can be distinguished. Results The results showed 8 principal components with a variance of 82.72 % in the database. The method creates new variables then used in the Cluster analysis indicating 7 clusters with 3 different facial types: Normal, prognathia inferior and brachygnathia inferior. Conclusion The brachygnathic facial type was mainly characterised as a shortened mandible, the upper jaw is not significantly involved. The correlations to the temporomandibular joint were shown. Molar and premolar malocclusions were revealed in two of three Clusters. Phenotypical distocclusion was not a single criterion for the affected sheep.